Hubungan Sensasi Frisson Pada Stimulus Musik Dengan Peningkatan Performa Intelegensi - Pamela Felycia Ardhinata; Yosef Purwoko; Yuriz Bakhtia; Maria Belladonna Rahmawati (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Intelligence affects someone in thinking and solving problems. Frisson sensation increase dopamine hormone production, activity and blood flow to the brain. Aim: To prove the association between frisson sensations on music stimulus and intelligence performance change. Methods: A quasy experimental study with one group pre- and post-test design was done to female medical students of Diponegoro University. A total of 30 participants were selected by purposive sampling technique. The stimulation was by listening to mp3 of 5 researcher-selected songs that last for 15 minutes in 3 consecutive days. The frisson measured by using a stopwatch. Intelligence performance before and after the frisson sensation was measured using Ravens Progressive Matrices, so that the difference could be calculated. The collected data was then analyzed using Wilcoxon test and simple linear regression. Result: The pre-test score had a median of 50.50 (30-56) and a post-test score of 54 (33-59), with a significant increase in RPM scores (p less than 0.001). The duration of frisson sensation had positive effect on RPM scores differences (p less than 0.001). Association between the duration and the score improvement could be formulated as: y = 0.047 + 2,711x. Conclusion: The frisson sensation on music stimulus can improve intelligence performance. The frisson that lasts longer will have more significant improvement on intelligence performance